Multi-agent Planning of the Network Traffic between Nanosatellites and Ground Stations. (2015) - Belokonov, Igor; Skobelev, Petr; Simonova, Elena; Travin, Vitaliy; Zhilyaev, Alexey
Abstract: Multi-agent technologies application for adaptive planning of communication sessions establishment requests with nanosatellites in the ground stations network in response to the arising events, considering constraints, is considered. Mathematical problem statement of adaptive communication sessions scheduling is given. Method of coupled interactions extension based on the demand-resource networks model for operative requests allocation for communication sessions between ground stations and nanosatellites implementation is described.